2019
DOI: 10.1021/acsomega.9b01864
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Formyl Fluoride Catalyzed by Sulfuric Acid and Formic Acid in the Atmosphere

Abstract: Formyl fluoride (HFCO) is an important atmospheric molecule, and its reaction with the OH radical is an important pathway when degradation of HFCO is considered in earth’s troposphere. Here, we study the hydrolysis of formyl fluoride (HFCO + H2O) with sulfuric acid (H2SO4) and formic acid (HCOOH) acting as catalysts by utilizing M06-2X, CCSD(T)-F12a, and conventional transitional state theory with Eckart tunneling to explore the atmospheric impact of the above-said hydrolysis reactions. Our calculated results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…The detailed expression of the trimolecules is provided by the reaction pathway HNO 3 •••H 2 O + HCHO as an example in the Supporting Information, and this reaction is similar to our previous studies in the HFCO + H 2 O + H 2 SO 4 72 and HCHO + H 2 SO 4 + HCOOH 51 reactions.…”
Section: Reaction Of Formaldehyde With Nitric Acidsupporting
confidence: 75%
“…The detailed expression of the trimolecules is provided by the reaction pathway HNO 3 •••H 2 O + HCHO as an example in the Supporting Information, and this reaction is similar to our previous studies in the HFCO + H 2 O + H 2 SO 4 72 and HCHO + H 2 SO 4 + HCOOH 51 reactions.…”
Section: Reaction Of Formaldehyde With Nitric Acidsupporting
confidence: 75%
“…Plentiful computational studies have also shown that DHAT reactions result in a catalytic effect. Examples include: (i) gas‐phase hydrolysis of HFCO is catalyzed by H 2 SO 4 ; (ii) decomposition of CF 3 OH is catalyzed by formic acid; (iii) SO 3 hydration is catalyzed by oxalic acid; (iv) SO 3 +NH 3 reaction is catalyzed by NH 3 , etc. Furthermore, double H‐atom exchange reactions of HO 2 +HX (X=F, Cl, Br, I) have also been predicted computationally …”
Section: Figurementioning
confidence: 99%
“…The reliability of the M06-2X functional and its wide application have been demonstrated in previous studies on the atmospheric reactions of sulfuric acid and sulfuric acid molecular clusters. 48–53 The calculated results of the corresponding frequencies of reactants, complexes, transition states, and products using M06-2X/MG3S suggest that all stable structures have positive frequencies, while the transition state has only one imaginary frequency. The stability of the density functional theory method has been tested by using the keyword (stable = opt).…”
Section: Methodsmentioning
confidence: 99%
“…The CH 3 CHO + H 2 SO 4 … (CH 3 ) 2 NH reaction occurs in one elementary step as depicted in Figure 1, which is similar to the hydrolysis of acetaldehyde catalyzed by sulfuric acid, as well as the reaction of formaldehyde with sulfuric acid catalyzed by formic acid and others. 34,36,50,51,53,81,82,83 It can be seen that when the H 2 SO 4 … (CH 3 ) 2 NH complex and CH 3 CHO act as reactants, the reaction occurs via the formation of prereaction complexes and then undergoes a unimolecular isomerization through these corresponding transition states responsible for the formation of post-reaction complex. In the CH 3 CHO + H 2 SO 4 … (CH 3 ) 2 NH reaction, there is a concerted reaction mechanism that the hydrogen atom of the OH group in sulfuric acid is transferred to the oxygen atom of the carbonyl group in CH 3 CHO by the amino group in dimethylamine, and simultaneously the oxygen atom of the S=O group in sulfuric acid is added to the carbon atom in CH 3 CHO, where dimethylamine is acted as a catalyst; this leads to the formation of the most stable post-reaction complex (CP1), which is a nucleation precursor of secondary organic aerosols.…”
Section: The Ch 3 Cho + H 2 So 4 Reaction Catalyzed By (Ch 3 ) 2 Nhmentioning
confidence: 99%